Heavenly Small Islands Simple Technology & Its Cultural Economy Impacts in Maluku, Indonesia: a New Proposed Multitasking Philosophy in Diversity (MPD) - Hendry I zaac Elim; Esther Kembauw; Reico H. Siahainenia; Jacobus S. A. Lamerkabel; Aphrodite M. Sahusilawane; Sri Wahyuni Djoko; Beni Setha (SCIENCE NATURE, 2019)
We will discuss a simple multitasking philosophy based on a close link among four (4) groups of scientific findings from the complicated forests, the shallow or deep seas, and the small islands future technologies, as well as its dramatically impacts in Maluku province economy. The results are then compared to world high multitasking technology system based on our proposed philosophy linked to biodiversity called as multitasking philosophy in diversity (MPD). The detail of simple explanations of such complicated multitasking diversity is presented. While the multitasking impacts in diversity of two to three different multidisciplinary fields are highlighted in a simple way step by step. This novel MPD has been analyzed to be able to increase the Maluku economy as large as 75%.